Relationship between swimming velocity and stroke parameters during the front-crawl - Tsunokawa, T.; Mankyu, H.; Ogita, F. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
Through pressure measurement and underwater motion capture analysis, the aim of this study was to clarify how propulsive forces, Froude efficiency, and stroke parameters change with swimming velocity during front-crawl swimming. Eight male swimmers performed 2 trials, once using pressure measurement and underwater motion capture analysis and once using a MAD system. In the analysis using pressure measurement and underwater motion capture, each swimmer performed 16-m front-crawl swimming 10 times at various velocities. During the trials, pressure forces acting on the hand and hand kinematics were analyzed to obtain the hand propulsive forces at each velocity. In the analysis using the MAD system, each swimmer performed 25-m front-crawl swimming 10 times at various velocities while pushing the pad set under the water, and the propulsive force at each velocity was obtained from the pushing force of the pad. This revealed that the mean propulsive force increased exponentially with the increase in mean swimming velocity, and the propulsive index n was 2.62 on average for the 8 participants. Maximal propulsive forces and maximal propulsive powers at maximum were significantly correlated with the results obtained using the MAD system. Froude efficiency varied considerably among the participants, being 0.54 ± 0.05 on average for all trials.